2019
DOI: 10.2147/ijn.s206899
|View full text |Cite
|
Sign up to set email alerts
|

<p>Targeted anticancer potential against glioma cells of thymoquinone delivered by mesoporous silica core-shell nanoformulations with pH-dependent release</p>

Abstract: Background and purpose Glioma is one of the most aggressive primary brain tumors and is incurable. Surgical resection, radiation, and chemotherapies have been the standard treatments for brain tumors, however, they damage healthy tissue. Therefore, there is a need for safe anticancer drug delivery systems. This is particularly true for natural prodrugs such as thymoquinone (TQ), which has a high therapeutic potential for cancers but has poor water solubility and insufficient targeting capacity. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
37
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 79 publications
6
37
0
Order By: Relevance
“…The specific surface area, total pore volume, and pore size were greatly decreased when particles were loaded with Pip, coated with GA, and conjugated to FA compared to the starting material for both HAPs and HAP-Ps. This observation is expected and in agreement with previous studies [30,31,36]. Interestingly, the pore size distributions calculated by BET method from N2 adsorption/desorption measurements showed that HAPs had a pore size ranging from 9 nm to 13 nm.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The specific surface area, total pore volume, and pore size were greatly decreased when particles were loaded with Pip, coated with GA, and conjugated to FA compared to the starting material for both HAPs and HAP-Ps. This observation is expected and in agreement with previous studies [30,31,36]. Interestingly, the pore size distributions calculated by BET method from N2 adsorption/desorption measurements showed that HAPs had a pore size ranging from 9 nm to 13 nm.…”
Section: Discussionsupporting
confidence: 92%
“…This observation can be explained by most Pip molecules being entrapped inside pores on the surface of HAPs. These results are in agreement with reports of loading drugs in mesoporous nanoparticles [30,31,63]. Changing the crystalline state of a water-insoluble drug to the non-crystalline state using mesoporous materials can enhance solubility, increasing the drug therapeutic activity [64].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations